Making methods rugged for regulated bioanalysis. (April 2015) - Unger, Steve; Horvath, Thomas; Tan, Melvin; Zhou, Jing; Lloyd, Thomas; McManus, Kevin; Wells, Edward
Methods started in discovery are optimized as they progress through preclinical and clinical development. Making a robust assay includes testing individual steps for consistency and points of failure. Assays may be transferred, optimized and revalidated several times. A rugged assay will not only meet regulatory requirements, but will execute with a low failure rate and confirm results under repeat analysis. Challenging aspects such as differential recovery, sample stabilization, resolution of isomers or conjugate analysis must be tackled and made routine. The proper selection of the IS can overcome limitations. It is best to know the potential points of failure before a study has started, but lessons learned from each study also provide invaluable insights to improve assay ruggedness.